Karakteristik dan identifikasi masalah interaktivitas Dalam pendidikan vokal daring - Zeng, Ming (RUBINSTEIN, 2024)
In recent years, the rapid development of Internet technology has significantly transformed the landscape of education, particularly in the field of vocal training. Online vocal education, once a niche offering, has gained substantial traction as a viable alternative to traditional face-to-face teaching. This shift was particularly pronounced during the COVID-19 pandemic, when in-person vocal lessons were largely replaced by online platforms. The adoption of online vocal education has surged due to its inherent advantages, such as convenience, flexibility, and the ability to share resources across diverse geographical locations. These advantages have made online learning an appealing option for both teachers and students alike. However, despite its benefits, online vocal education presents several challenges, particularly in terms of interactivity. This article utilizes a SWOT analysis to examine the strengths, weaknesses, opportunities, and threats associated with online vocal classrooms. The analysis reveals that while online vocal education allows for greater accessibility and resource sharing, it also faces limitations in terms of real-time feedback, student-teacher interaction, and the difficulty of providing personalized instruction in a virtual setting. The lack of physical presence can hinder non-verbal communication cues that are often crucial in vocal training. Additionally, issues such as technological barriers, internet connectivity, and the potential for distractions in a home environment can negatively impact the learning experience. In conclusion, online vocal education offers promising opportunities for expanding access to quality vocal training, but it also requires further innovations to enhance its interactivity. Addressing these challenges could pave the way for more effective online learning models, making it a more seamless and rewarding experience for vocal students and educators